A Hospital-Based Study to Assess the Effect on Mental Health of Mothers providing Kangaroo Mother Care (KMC) to Newborns - Vidhwani, Harshita; Anand, Shweta; Goutam, Pritesh (Indian Journal of Child Health, 2025)
Background: Many mothers with low-birth-weight babies and sick babies present with mental health issues. Kangaroo mother care (KMC) aims at skin-to-skin contact between the care provider and newborn babies. KMC provides psychological support to the mother and helps her positively interact with the baby. Method: This present cross-sectional observational study assessed the mental health of 40 KMC mothers according to the DASS-21 questionnaire. Mothers filled the questionnaire before the start of KMC and after 7 days of continuing Kangaroo care sessions. The questionnaire assessed the mental health on three different parameters: stress, anxiety and depression. Both the baseline and follow-up scores were computed, and the data were analysed. Results: There was a significant reduction in scores of stress, anxiety and depression over 7 days of KMC sessions. Conclusion: Kangaroo Mother Care supports bonding and interaction between mothers and babies. The mental health of mothers improves after KMC sessions.